A spectroscopic mechanistic study on zirconium(iv) and hafnium(iv) complexes - Mphure, Lebohang Theodore (University of the Free State, 2015)
The aim of this study was to synthesize M(L,L’)4 type complexes of zirconium(IV) and hafnium(IV) using N,N’-diamine and O,O’-bidentate ligands. The synthesized complexes were characterized and a kinetic study of the formation of the respective complexes was performed. Characterization of the successfully synthesized complexes, tetrakis(thenoyltrifluoro-acetylacetone) zirconium(IV) monohydrate ([Zr(tta)4].H2O) and tetrakis(thenoyltrifluoroacetylacetonato) hafnium(IV) ([Hf(tta)4]) was done by infrared (IR), ultraviolet and visible spectroscopy (UV/Vis) and 1H and 19F nuclear magnetic resonance (NMR) spectroscopy. The structure of [Zr(tta)4]∙H2O was successfully characterized by single crystal X-ray diffraction while its hafnium counterpart was unsuccessful due to poor crystal quality. [Zr(tta)4].H2O crystallized in the orthorhombic space group Pca21 with Z = 4. The structure of [Zr(tta)4].H2O consists of a zirconium(IV) metal centre coordinated to eight oxygen atoms of four O,O’-bidentate ligands, with an average Zr—O bond distance of 2.18(7) Å and an average bite angle of 107(8)˚. Unlike common alternating CF3 groups with respect to the coordinating ligand, the CF3 groups of this structure were clustered in the plane of the molecule. In contrast to a similar structure the thenoyl rings of this structure were connected by a water molecule. In the kinetic investigations the formation reaction between zirconium(IV) and hafnium(IV) with the Na(tta) ligand at varying metal to ligand ratios were followed by 19F and 1H-NMR. Competition studies were also performed between the two metals and Na(tta). In both the studies the a general observation was made that the formation reaction consisted of two reactions: a fast first reaction and a slow second reaction. In the individual metal studies it was determined that the observed rate constants for the hafnium(IV) system were ~ 2 times faster than the zirconium(IV) system for the first fast reaction and ~ 7 times faster for the second slow reaction. In the competition studies between zirconium(IV) and hafnium(IV) integration values of the final spectra showed that more of [Zr(tta)4].H2O was formed compared to [Hf(tta)4] was formed. The observed rate constants for both the fast and the slow reaction were comparable in each case and didn’t reflect the observations that were made for the individual metal kinetic runs.

Die doel van hierdie studie was om van M(L,L’)4 tipe komplekse van sirkonium(IV) en hafnium(IV) te sintetiseer met N,N’-diamien en O,O’-bidentate ligande. Die gesintetiseerde komplekse is gekarakteriseer en `n kinetiese studie rakende die vorming van die onderskeie komplekse is uitgevoer. Karakterisering van die gesintetiseerde komplekse, tetrakis(tenoïeltrifluoor-asetielasetoon) sirkonium(IV) monohidraat ([Zr(tta)4].H2O) en tetrakis(tenoïeltrifluoorasetielasetoon) hafnium(IV) ([Hf(tta)4]) is uitgevoer deur middel van infrarooi (IR), ultraviolet en sigbare spektroskopie (UV/Vis) en 1H en 19F kermagnetiese resonans (KMR) spektroskopie. Die struktuur van [Zr(tta)4].H2O is suksesvol deur enkelkristal X-straal diffraksie gekarakteriseer terwyl die karakterisering van die hafnium eweknie enkelkristal diffraksie met X-straal onsuksesvol was as gevolg van swak kristalkwaliteit. [Zr(tta)4].H2O Dit het gekristalliseer in die ortorombiese ruimtegroep Pca21 met Z = 4. Die [Zr(tta)4].H2O kompleks bestaan uit `n sirkonium(IV) metaalkern wat aan die agt suurstofatome van die vier O,O’-bidentate ligande gekoördineer is, met `n gemiddelde Zr—O bindingsafstand van 2.18(7) Å en `n gemiddelde bythoek van 107(8)˚. In teenstelling met algemene variasies in die CF3 groepe ten opsigte van die koördinerende ligand, groepeer die CF3 groepe van hierdie struktuur aan die dieselfde kant van die molekuul. Anders as in soortgelyke gepubliseerde strukture word die tenoïelringe van hierdie struktuur met `n water molekuul verbind. Vir die kinetiese ondersoek is die vormingsreaksie tussen sirkonium(IV) en hafnium(IV) met die Na(tta) ligand met wisselende metaal:ligand verhoudings deur middel van 19F en 1H KMR gevolg. Kompetisiestudies is uitgevoer tussen die twee metale en die Na(tta) ligand. In beide die studies is die algemene waarneming gemaak dat die vormingsreaksie uit twee reaksies bestaan: `n vinnige eerste reaksie en `n stadige tweede reaksie. In die individuele metaalstudies is vasgestel dat die waargenome tempokonstantes vir die hafnium(IV) reaksies ~ 2 keer vinniger is as die sirkonium(IV) reaksies vir die eerste, vinnige reaksie, en ~ 7 maal vinniger vir die tweede, stadige reaksie. In die kompetisiestudies tussen sirkonium(IV) en hafnium(IV) het integrasiewaardes van die finale spektra getoon dat meer [Zr(tta)4] as [Hf(tta)4] gevorm het. Die waargenome tempokonstantes vir beide die vinnige en stadige reaksies was vergelykbaar in elke geval en weerspieël nie die waarnemings wat vir die individuele metaal studies gemaak is nie.
Dissertation (M.Sc. (Chemistry))--University of the Free State, 2015
Keywords: Zirconium -- Synthesis; Zirconium compounds -- Synthesis; Hafnium compounds; Hafnium compounds -- Synthesis